2007
DOI: 10.1128/aem.00201-07
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a Thermophilic Synechococcus Isolate from the Microbial Mat of Octopus Spring to Light

Abstract: Thermophilic cyanobacteria of the genus Synechococcus are major contributors to photosynthetic carbon fixation in the photic zone of microbial mats in Octopus Spring, Yellowstone National Park. Synechococcus OS-B was characterized with regard to the ability to acclimate to a range of different light irradiances; it grows well at 25 to 200 HL]), we noted several responses that had previously been associated with HL acclimation of cyanobacteria, including cell bleaching, reduced levels of phycobilisomes and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 48 publications
4
38
0
2
Order By: Relevance
“…For instance, closely related Synechococcus 16S rRNA sequences designated A 00 , A 0 , A, B 0 and B, were detected at progressively lower temperatures from about 701C to about 501C, respectively Ward et al, 1998). Furthermore, recent experiments with Synechococcus isolates representing some of these 16S rRNA sequences suggest that they are physiologically adapted to temperature ranges and light intensities experienced in situ (Allewalt et al, 2006;Kilian et al, 2007). There is also evidence of vertical stratification of Synechococcus populations within the microbial mats.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, closely related Synechococcus 16S rRNA sequences designated A 00 , A 0 , A, B 0 and B, were detected at progressively lower temperatures from about 701C to about 501C, respectively Ward et al, 1998). Furthermore, recent experiments with Synechococcus isolates representing some of these 16S rRNA sequences suggest that they are physiologically adapted to temperature ranges and light intensities experienced in situ (Allewalt et al, 2006;Kilian et al, 2007). There is also evidence of vertical stratification of Synechococcus populations within the microbial mats.…”
Section: Introductionmentioning
confidence: 93%
“…Because the mat Synechococcus populations have been extensively characterized at the level of rRNA diversity and physiology, and are available as isolates, they provide optimal starting material for high-resolution molecular analyses to establish links between physiological differences, niche partitioning strategies and microbial diversity within the mat community (Steunou et al, 2006;Kilian et al, 2007). Here, we present our approach in which we sequenced the genomes of two isolates of Synechococcus derived from different temperature regions of the mat.…”
Section: Introductionmentioning
confidence: 99%
“…These isolates are differentially distributed along the horizontal thermal gradient of the mat. Syn OS-B 0 is prevalent at 53-60 1C whereas Syn OS-A dominates at higher temperatures (58-65 1C) (Allewalt et al, 2006;Kilian et al, 2007). In recent studies we showed that both Syn OS-A and Syn OS-B 0 contain an extensive suite of genes in the Pho regulon, which is required for efficient acquisition of P (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 94%
“…Axenic cultures of Syn OS-A (CIW 14) were isolated from original enrichment cultures using the same strategy as described by Kilian et al (2007). Cultures were grown and maintained at 50 1C in liquid D medium supplemented with 10 mM HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (pH 8.2-8.3)) and Va vitamins.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…The mat communities are ideal for such analyses: (i) they have an uneven community structure skewed toward large, predominant type-A/B Synechococcus populations, (ii) genetically and ecologically relevant isolates, both axenic and nonaxenic, of the type-A/B populations are available (Allewalt et al, 2006;Kilian et al, 2007), (iii) the mats have well-defined temperature, light and chemical gradients that can be measured at the microscale level using microsensors that can also quantify photosynthesis and other microbial activities in situ (Ward et al, 2006) (Figure 1), (iv) these gradients can be experimentally subsampled (Ramsing Environmental genomics and microbial species DM Ward et al et al, 2000;Ferris et al, 2003), (v) the mats have very high biomass, are readily accessed, and are protected within Yellowstone National Park, (vi) there is background information on the predominance and distribution of the specific 16S rRNA and ITS genotypes in the mat and (vii) previous studies have explored cyanobacterial physiology over the diel cycle (for example, van der Meer et al, 2005van der Meer et al, , 2007. This strong foundation allows for the development of rational hypotheses related to studies of acclimation and adaptation within and between putative ecotype populations.…”
Section: Our Integrated Theory-based Approachmentioning
confidence: 99%